Stress path during pressuremeter test and link between shear modulus and Menard pressuremeter modulus in unsaturated fine soils - Savatier Vincent; Savatier Maxime (E3S Web of Conferences, 2016)
This paper presents the stress path before and during a pressumeter test using a Modified Cam-Clay model. This model have been used for unsaturated clay with continuous water phase (D2 domain according to Boutonnier 2007) and for silty to clayey soils with discontinuous water phase (D1 domain – ibid.). After reminding the stress distribution around a pressuremeter cell and the meaning of the Menard pressuremeter modulus which is linked to the soil shear modulus, we explain the stress state during pressuremeter modulus measurement. Then, we show that this stress path diagram can be used to explain classical observations made using Menard pressuremeter tests in continental area and typically: